Effect of Occlusal Splints on the Temporomandibular Disorders, Dental Wear and Anxiety of Bruxist Children - Restrepo, Claudia C; Medina, Isabel; Isabel, Patiñob (European Journal of Dentistry, 2011)
Objectives: To evaluate the effectiveness of occlusal splints to reduce the signs and symptoms of temporomandibular disorders (TMD), dental wear and anxiety in a group of bruxist children. Methods: All of the subjects were 3 to 6 years old, had complete primary dentition, class I occlusion and were classified as bruxist according to the minimal criteria of the ICSD for bruxism. For each child, anxiety was evaluated with the Conners’ Parent Rating Scales (CPRS). The TMD were evaluated using the RDC/TMD. The dental wear was processed in digital format with Mat Lab® and Lab view® software to determine its size and form. The children were randomized into an experimental (n=19) and a control (n=17) group. The children in the experimental group used rigid bite plates for a two-year period, until mixed dentition. Afterwards, the CPRS and the RDC/TMD were applied again and dental casts were taken. Comparisons of the variables regarding dental wear, signs and symptoms of TMD and anxiety before and after treatment among the groups were analyzed using the t-test, the Wilcoxon rank sum test and the Mann-Whitney test. Results: The subjects in the experimental group showed no statistically significant difference regarding anxiety levels and dental wear when compared with the control group. The signs and symptoms of TMD were not reduced except for the deviation in mouth opening. Conclusions: The use of rigid occlusal bite plates was not efficient in reducing the signs of bruxism as a whole but did reduce the deviation in mouth opening. (Eur J Dent 2011;5:441-450)
Keywords: Bruxism; Rigid occlusal bite plates; TMD; Dental wear; Anxiety